2011
DOI: 10.1007/s10811-011-9671-6
|View full text |Cite
|
Sign up to set email alerts
|

A new screening for hemagglutinins from Vietnamese marine macroalgae

Abstract: Aqueous extracts from 42 species of Vietnamese marine macroalgae, including 17 Chlorophyta, 22 Rhodophyta, and three Phaeophyta species, were examined for hemagglutination activity using native and enzyme-treated different animal and human erythrocytes. All extracts agglutinated at least one type of erythrocytes tested. Strong activity was detected in extracts from four Chlorophyta (Caulerpa serulata var. boryana, Caulerpa sertularioides f. longipes, Halimeda velasquezii, and Halimeda discoidea) and two Rhodop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 32 publications
2
12
0
6
Order By: Relevance
“…However, we found that the HA of P. minor was stable on a wide range of pH and temperature. Lectin of Dictyospheria versluysii green algae was also reported stable in a wide range of temperature and pH (Hung et al, 2012). The HA of P. minor protein extract was not affected by the presence of chelating agent EDTA, indicating that it did not require divalent cation to maintain its biological activity (Oliveira et al, 2002).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…However, we found that the HA of P. minor was stable on a wide range of pH and temperature. Lectin of Dictyospheria versluysii green algae was also reported stable in a wide range of temperature and pH (Hung et al, 2012). The HA of P. minor protein extract was not affected by the presence of chelating agent EDTA, indicating that it did not require divalent cation to maintain its biological activity (Oliveira et al, 2002).…”
Section: Resultsmentioning
confidence: 93%
“…However, up till now, report on brown algae lectin is still limited. Only few publications reported the screening of brown algae lectin (Anam, Praseptiangga, Fajarningsih, & Intaqta, 2016;Fajarningsih, Intaqta, Praaseptiangga, Anam, & Chasanah, 2018;Fajarningsih et al, 2015;Freitas et al, 1997;Hung et al, 2012) and to our knowledge only one publication reported the purification of brown algae lectin, an HFL lectin isolated from Hizikia fusiformis (Wu, Tong, Wu, Liu, & Li, 2016). According to Harrysson et al (2018), isolation of lectin or other protein from brown algae is difficult due to the high content of non-protein interfering compounds such as polyphenols and viscous polysaccharide.…”
Section: Introductionmentioning
confidence: 99%
“…Hemagglutinin, aglutinin atau lektin merupakan protein non imun alami yang mengikat karbohidrat secara reversible dan mempunyai kemampuan dalam mengaglutinasi sel atau mengikat polisakarida dan glikoprotein (Goldstein et al, 1980;Le Hung et al, 2012). Penekanan pada non-imun, dimaksudkan untuk membedakan lektin dari antibodi-karbohidrat tertentu, seperti kinase, glicosidase, transferase ataupun transporter (Goldstein et al, 1980).…”
Section: Pendahuluanunclassified
“…Dapat dilihat pada Tabel tersebut, eritrosit kelinci lebih sensitif untuk mendeteksi adanya aktivitas hemagglutinasi dibandingkan dengan eritrosit manusia. Berdasarkan penelitian Le Hung et al (2012), eritrosit kelinci memiliki sensitivitas paling tinggi untuk mendeteksi aktivitas hemagglutinasi lektin makroalga, kemudian disusul oleh eritrosit domba, ayam, manusia (A,B,O) dan kuda. Hasil tersebut, sedikit berbeda dengan yang dilaporkan oleh Freitas et al (1997) yang menunjukkan bahwa eritrosit domba justru paling sensitif untuk mendeteksi aktivitas hemagglutinasi ekstrak alga yang dipelajari.…”
Section: Hasil Dan Bahasanunclassified
See 1 more Smart Citation